The Umno-Pas Informal Pact in Malaysia’s Fourteenth General Election: The Good Plan that Went Wrong - Mohamed, Nik Mawardi; Haji Yusoff, Kamarul Zaman; Omar, Rusdi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
The Malaysian ruling coalition, Barisan Nasional (BN), seemed to have a hard time facing the fourteenth General Election (GE) in 2018 that its Chairman cum Prime Minister, Datuk Seri Najib Razak, was widely reported as early as 2015 to be deeply embroiled in a major financial scandal involving Malaysian Government’s investment arm, 1Malaysia Development Berhad (1MDB), with allegations that billions were diverted from that company for personal usage of Najib, his family members and his cronies. The allegation that Najib received a mysterious RM2.6 billion payment into his personal bank account, which was initially revealed by the the Sarawak Report, followed by the more reputable Wall Street Journal, was particularly very damaging. It led to the removal of the Attorney General (AG), who headed a special task force to investigate it, besides the removal of three senior UMNO leaders, who were highly critical of it, from their government and party posts. During this time, the opposition coalition, Pakatan Rakyat (PR), was having trouble due to the uneasiness of PAS over the attempt by PKR to replace its Menteri Besar of Selangor with its de facto leader, Datuk Seri Anwar Ibrahim, via a forced Kajang byelection, without consulting PAS first. The trouble became greater after Najib’s own Minister at the Prime Minister’s Office assured PAS that the Federal Government would give way for Kelantan to implement hudud, prompting PAS to submit a Private Member’s Bill to amend the Syariah Courts (Criminal Jurisdiction) Act 1965 to the Parliament, which resulted in the eventual dissolution of PR. The easy wins of BN over a new opposition coalition, Pakatan Harapan (PH), due to the inclusion of PAS as third candidates, in Kuala Kangsar and Sungai Besar by-elections convinced UMNO that it would win the fourteenth GE in three-cornered fights, hence the efforts by UMNO to make the appearance that it was supportive of PAS’s struggle. PAS, meanwhile, believed that BN would not do that well in the fourteenth GE and needed its help to form the government, hence the cries by PAS that it would be a king-maker. However, in the end, three-cornered fights was not enough for UMNO and PAS when BN and PAS just managed to get 79 and 18 seats respectively out of 222 offered seats. This paper studies the main factor that made BN lost despite the seemingly feasible plan of threecornered fights.